PERBANDINGAN TINGKAT KESEGARAN JASMANI SISWA KELAS X IPS SMA NEGERI 1 RENGAT BARAT DAN SISWA KELAS X FARMASI SMK KESEHATAN HAR-KAUSYAR KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Deci Aprilita; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is satiety during learning, so the learning process of exercise in class X IPS SMA Negeri Rengat Barat and class X Pharmacy at SMK Kesehatan Han-Kausyar is not optimal, which is not always done. Don't get better. The purpose of this study was to determine whether there is a comparison between the physical fitness of the two schools for these students. The population in this research consisted of male students of class X IPS and male students of class X pharmacy, a total of 55 persons. The sampling technique used cluster random sampling where the sampling was performed in the area with a sample of 15 students from West Rengat Barat High School and 12 Han-Kausyar Health Vocational Schools. The tools used in this study were the 60-meter walk test, 60-second pull-up, 60-second sit-up, vertical jump, 1200-meter run. The data obtained was analyzed using the independent "t" significance test technique. Based on the results of research and data processing using statistical research procedures, the data normality test analysis at SMA Negeri Rengat Barat Lhitung yields equal to 0.122 and Ltable 0.220, which means Lhitung <Ltable. Meanwhile, Han-Kausyar Health Vocational High School produced Lhitung 0.166 and Ltable 0.242. This means that Lhitung <Ltable. then the data will be distributed normally. In addition, after the t-test was performed, it was found that tcount (0.245) <ttable (2,262), where Ho was rejected, it could be concluded that there was no comparison between male students of SMA Negeri 1 Rengat Barat and class X Pharmacy at SMK Kesehatan Han-Kausyar.Key Words: Physical fitness level, students from SMA Negeri 1 Rengat Barat, students fromSMK Kesehatan Han-Kausyar